Sliding member and internal combustion engine
By using titanium-containing copper-based alloy particles in the sliding member and forming a titanium oxide layer, the problem of insufficient wear resistance in high temperature environment is solved, and excellent wear resistance and sliding properties of the sliding member are achieved.
Patent Information
- Application Number
- CN202380039229.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-04-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing sliding parts lack wear resistance in high-temperature gas environments, especially in conditions exceeding 1000°C, and there is room for improvement.
Titanium-containing copper-based alloy particles are used as the constituent material of the sliding film, and a titanium oxide layer is formed at the particle interface, and the substrate is blown to the cold spraying technology to form a dense sliding film to improve wear resistance.
Excellent wear resistance under high temperature environments are achieved. The presence of the titanium oxide layer prevents the aggregation and plastic flow of copper-based alloy particles, and improves the wear resistance and sliding properties of the sliding parts.
Smart Images

Figure CN119256116A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sliding component and an internal combustion engine, and more particularly, to a sliding component capable of achieving excellent high-temperature wear resistance and an internal combustion engine including the sliding component. Background Art
[0002] In the past, Patent Document 1 disclosed a valve seat (valve seat) for an internal combustion engine that uses a sliding component formed by blowing precipitation-hardening copper alloy particles such as Cu-3Ni-0.7Si onto a substrate. In this precipitation-hardening copper alloy, Ni is generated for the purpose of strengthening precipitation. 2 Si, while containing Si reduces cohesive wear through its thinner oxide film.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6519962
[0006] Problems to be solved by the invention
[0007] However, when the sliding member described in Patent Document 1 is applied to an exhaust valve seat of an internal combustion engine exposed to high-temperature gas exceeding 1000° C., for example, the high-temperature wear resistance is low and there is room for improvement. Summary of the invention
[0008] The present invention has been made in view of the problems in the prior art, and an object of the present invention is to provide a sliding component capable of achieving excellent high-temperature wear resistance and an internal combustion engine including the sliding component.
[0009] The present inventors have conducted intensive studies to achieve the above object and have found that the predetermined sliding film contains copper-based alloy particles containing titanium and that the above object is achieved by having a titanium oxide layer on a part of the interface between the particles forming the sliding film, thereby completing the present invention.
[0010] That is, the sliding member of the present invention has a sliding film at least on the surface. The sliding film contains copper-based alloy particles containing titanium, and has a titanium oxide layer at a part of the interface between the particles forming the sliding film.
[0011] Furthermore, an internal combustion engine according to the present invention is characterized by including the above-mentioned sliding member.
[0012] Effects of the Invention
[0013] According to the present invention, since the sliding film contains copper-based alloy particles containing titanium and has a titanium oxide layer at a portion of the interface between the particles forming the sliding film, a sliding part capable of achieving excellent high-temperature wear resistance and an internal combustion engine including the sliding part can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a cross-sectional view schematically showing a first embodiment of the sliding component of the present invention.
[0015] Figure 2 It is a cross-sectional view schematically showing a second embodiment of the sliding component of the present invention.
[0016] Figure 3 This is a partial cross-sectional view schematically showing a part of one embodiment of the internal combustion engine of the present invention.
[0017] Figure 4 This is a scanning electron microscope image of a cross section of the sliding film in Example 1. DETAILED DESCRIPTION
[0018] Hereinafter, the sliding component and the internal combustion engine of the present invention will be described in detail with reference to the accompanying drawings. In addition, the dimensional ratios of the drawings cited below are exaggerated for the sake of convenience of description and may be different from the actual ratios.
[0019] (Sliding parts)
[0020] [First embodiment]
[0021] like Figure 1 As shown, the sliding component 1 of the first embodiment includes: a substrate 10 and a sliding film 20 formed on the surface of the substrate 10. The sliding film 20 includes copper-based alloy particles 21 containing titanium as particles (grains) constituting the sliding film 20, and has a titanium oxide layer 23 on a part of the interface 20a between the particles constituting the sliding film 20. In addition, the sliding film 20 has cavities 20b. In addition, it is of course possible to use the surface 20c of the sliding film 20 as a sliding surface.
[0022] Here, in the present invention, "copper-based alloy" refers to an alloy containing copper as a main component, and its content is the largest among all components in terms of mass %. The same is true for each alloy of iron-based alloy, cobalt-based alloy, molybdenum-based alloy, chromium-based alloy, and nickel-based alloy, and refers to an alloy containing each metal as a main component, and its content is the largest among all components in terms of mass %.
[0023] In the present invention, the "titanium oxide layer" refers to the titanium contained in the copper-based alloy particles, which is present near the surface of the copper-based alloy particles and is easily exposed to an oxidizing atmosphere such as the air, and is formed by oxidation in an oxidizing atmosphere such as the air. Therefore, the copper-based alloy particles that already contain titanium at the stage of the obtained raw material particles have a titanium oxide layer on their surface.
[0024] According to this embodiment, since the sliding film 20 includes copper-based alloy particles 21 containing titanium and has a titanium oxide layer 23 at a portion of the interface 20a between the particles forming the sliding film 20, it is difficult to soften even at high temperatures, and excellent high-temperature wear resistance can be achieved.
[0025] In the past, when particles are blown onto a substrate by cold spraying to form a sliding film on the substrate, it is preferred that the oxide film on the surface of the particles is thin or non-existent. When the particles are blown onto the substrate by cold spraying, plastic deformation occurs, destroying the oxide film, and the metallurgical bonding between the particles is better.
[0026] In contrast, in the present invention, an oxide film is actively formed on the particle surface by making copper contain titanium, an easily oxidizable metal. When such titanium-containing copper-based alloy particles are used as raw material particles for cold spraying, the relatively soft copper alloy particles are blown onto the substrate by cold spraying and plastic deformation occurs, a part of the oxide film is destroyed, and the alloy particles are metallurgically bonded to each other, while a part of the oxide film remains intact. Such an oxide film has always been considered to hinder the effect of improving wear resistance, but it has been found that it exhibits an excellent effect of improving wear resistance at high temperatures.
[0027] Hereinafter, the currently estimated mechanism for improving the high-temperature wear resistance of sliding parts will be described in detail.
[0028] For example, when a sliding film is formed by titanium-containing copper-based alloy particles, a titanium oxide layer present in a portion of the interface between particles forming the sliding film is more easily and uniformly dispersed in the sliding film than hard particles when the sliding film is formed by copper-based alloy particles and hard particles. Therefore, it is believed that such a titanium oxide layer is likely to effectively exhibit a pinning effect on the plastic flow in the sliding film, can inhibit the aggregation of titanium-containing copper-based alloy particles, and improve the high-temperature wear resistance of the sliding part.
[0029] In addition, for example, the above-mentioned titanium oxide layer is likely to be contained in a larger amount in the sliding film than the precipitates contained in the copper alloy particles in the case of forming the sliding film using precipitation-hardening copper alloy particles. Therefore, it is also believed that such a titanium oxide layer is likely to effectively exhibit a pinning effect on the plastic flow in the sliding film, and can inhibit the aggregation of the copper-based alloy particles containing titanium, thereby improving the high-temperature wear resistance of the sliding part.
[0030] Furthermore, for example, when the sliding part slides, the titanium oxide layer can easily relieve the stress applied to the copper-based alloy particles containing titanium at the interface between the particles forming the sliding film. Therefore, it is also believed that such a titanium oxide layer can easily suppress the aggregation of the copper-based alloy particles containing titanium, and can improve the high-temperature wear resistance of the sliding part.
[0031] However, as the sliding part of the present invention, it is sufficient to have the above-mentioned structure (for example, refer to paragraph 0015), and even if the same effects are obtained by mechanisms other than the above-mentioned mechanism, they are of course included in the scope of the present invention.
[0032] Furthermore, according to the present embodiment, the titanium oxide itself forming the titanium oxide layer functions as a solid lubricant on the surface side of the sliding film, improves the sliding properties of the sliding member, and can enhance the wear resistance.
[0033] Here, the specifications and material types of each constituent element are described in more detail.
[0034] (Base material)
[0035] The substrate is not particularly limited, and for example, metals conventionally used as sliding parts of internal combustion engines may be used. However, aluminum alloys have high thermal conductivity and can be preferably used.
[0036] Examples of the aluminum alloy include A5056, A1050, AC2A, AC8A, ADC12, and AC4CH specified in Japanese Industrial Standards.
[0037] (Sliding Film)
[0038] The sliding film is preferably formed of, for example, a particle aggregate. Here, in the present invention, "particle aggregate" means a material in which particles are not completely dissolved but the surface of the particles is partially softened or dissolved, and the contact portions of adjacent particles are solidified and bonded to form an integrated body.
[0039] The sliding film preferably has a porosity of 4% by area or less, more preferably 1% by area or less, in its cross section. The fewer and denser the pores, the greater the strength of the sliding film and the higher the high-temperature wear resistance of the sliding component.
[0040] The porosity of the sliding film can be calculated by, for example, binarizing a scanning electron microscope image by image processing and analyzing the image.
[0041] Furthermore, the sliding film preferably has at least one of amorphous and nanocrystals at the interface between particles forming the sliding film. By forming fine nanocrystals and amorphous materials near the interface between particles, the wear resistance of the sliding part can be improved.
[0042] The amorphous substance and nanocrystals at the interface between particles can be confirmed by, for example, electron beam backscatter diffraction using a scanning electron microscope, projecting the diffraction pattern onto a detector surface, and analyzing the crystal orientation based on the projected pattern.
[0043] In addition, the sliding film is preferably formed by blowing particles forming the sliding film onto a substrate and deforming the particles. By forming the sliding film in this way, the wear resistance of the sliding part can be improved.
[0044] (Copper-based alloy particles)
[0045] As the above-mentioned copper-based alloy particles, as long as they contain titanium and can show the effect of improving the high-temperature wear resistance of the sliding parts, there is no particular restriction. For example, the titanium content in the copper-based alloy particles is preferably more than 1.0 mass % and less than 15.0 mass %. When the titanium content in the copper-based alloy particles is less than 1.0 mass %, it is possible that a titanium oxide layer for fully improving the high-temperature wear resistance of the sliding parts cannot be formed. On the other hand, when the titanium content in the copper-based alloy particles exceeds 11.0 mass %, it is possible that titanium cannot be uniformly dispersed in the copper-based alloy particles. In addition, when the titanium content in the copper-based alloy particles exceeds 15.0 mass %, it is possible to form a titanium oxide layer on the entire interface between the particles constituting the sliding film.
[0046] From the viewpoint of being able to more reliably improve the high-temperature wear resistance of the sliding member, the titanium content in the copper-based alloy particles is preferably 3.5 mass % or more and 11.0 mass % or less.
[0047] In addition, if the titanium content in the copper-based alloy particles exceeds 9.0 mass%, the effect of improving high-temperature wear resistance tends to approach a saturation state. Therefore, from the viewpoint that a titanium oxide layer can be effectively dispersed and formed at the interface between particles forming a sliding film, thereby more reliably improving the high-temperature wear resistance of the sliding part, the titanium content in the copper-based alloy particles is preferably 3.5 mass% or more and 9.0 mass% or less.
[0048] Furthermore, from the viewpoint of more effectively dispersing and forming a titanium oxide layer at the interface between particles forming the sliding film and more reliably improving the high-temperature wear resistance of the sliding part, the titanium content in the copper-based alloy particles is preferably 3.5 mass % or more and 8.0 mass % or less.
[0049] Furthermore, from the viewpoint of effectively forming a titanium oxide layer functioning as a solid lubricant on the surface side of the sliding film and improving the wear resistance of the sliding part at high temperatures, the titanium content in the copper-based alloy particles is preferably 4.0 mass % or more and 10.0 mass % or less.
[0050] In particular, from the viewpoint that a titanium oxide layer can be more effectively dispersed and formed at the interface between particles forming a sliding film, and a titanium oxide layer that functions as a solid lubricant can be effectively formed on the surface side of the sliding film, thereby more reliably improving the high-temperature wear resistance of the sliding part, the titanium content in the copper-based alloy particles is preferably 4.0 mass% or more and 8.0 mass% or less.
[0051] The titanium-containing copper-based alloy particles may contain aluminum. The aluminum content in the titanium-containing copper-based alloy particles is preferably, for example, 0.5 mass % or less.
[0052] The titanium-containing copper-based alloy particles preferably contain precipitates composed of copper and titanium. Examples of such precipitates include Cu 4 When such precipitates are contained in the copper-based alloy particles containing titanium, the wear resistance of the sliding parts can be improved by strengthening precipitation of the alloy particles themselves.
[0053] Such precipitates can be confirmed by observing the cross section of the titanium-containing copper-based alloy particles using an energy dispersive X-ray analyzer and a transmission electron microscope.
[0054] The average particle size (equivalent circle diameter) of the titanium-containing copper-based alloy particles is preferably 20 μm to 50 μm, more preferably 20 μm to 40 μm. If the average particle size of the titanium-containing copper-based alloy particles is less than 20 μm or exceeds 50 μm, it may not be possible to form a desired sliding film with good yield.
[0055] The average particle size (equivalent circle diameter: the diameter of a circle having the same area as the projected area of the particle image) of the titanium-containing copper-based alloy particles can be calculated by binarizing a scanning electron microscope image by image processing and analyzing the image.
[0056] (Titanium oxide layer)
[0057] As the titanium oxide layer, there is no particular limitation as long as it can show the effect of improving the high-temperature wear resistance of the above-mentioned sliding parts. In addition, the titanium oxide layer is not formed separately on the surface of the copper-based alloy particles, but is formed by oxidation of the titanium in the titanium-containing copper-based alloy particles as described above, which is present near the surface that is easily in contact with an oxidizing atmosphere such as the atmosphere. Such a titanium oxide layer appears to be linear in the cross section of the sliding film. The length of the linear titanium oxide layer depends on the size of the titanium-containing copper-based alloy particles, for example, preferably 10 μm or more and 40 μm or less, more preferably 15 μm or more and 35 μm or less. In addition, the width of the linear titanium oxide layer is preferably 0.05 μm or more and 2 μm or less, more preferably 0.1 μm or more and 1 μm or less. In the case where the length of the titanium oxide layer is less than 10 μm or the width is less than 0.05 μm, the effect of improving the high-temperature wear resistance may be weakened. In the case where the length of the titanium oxide layer exceeds 40 μm or the width exceeds 2 μm, it may not be possible to form the desired sliding film with good yield.
[0058] The titanium oxide layer described above can be confirmed by observing the cross section of the sliding film using a scanning electron microscope and an energy dispersive X-ray analyzer.
[0059] Figure 2 1 and 2 are diagrams for explaining a second embodiment of the sliding member of the present invention. In the following embodiments, the same reference numerals are given to the same components as those of the first embodiment, and detailed descriptions thereof are omitted.
[0060] [Second embodiment]
[0061] like Figure 2 As shown, the sliding component 2 of the second embodiment has the same structure as the sliding component 1 of the first embodiment, except that the sliding film 20 further includes metal particles 25 and / or ceramic particles 25 containing at least one metal selected from the group consisting of iron, cobalt, molybdenum, chromium and nickel.
[0062] Next, the advantages of this embodiment will be described.
[0063] According to this embodiment, since the sliding film 20 also includes metal particles 25 and / or ceramic particles 25 containing at least one metal selected from the group consisting of iron, cobalt, molybdenum, chromium and nickel, in addition to the advantages of the first embodiment, better high-temperature wear resistance can be achieved, and thermal conductivity can be ensured.
[0064] (Metal particles, ceramic particles)
[0065] The metal particles or ceramic particles are not particularly limited, but are preferably harder than the titanium-containing copper-based alloy particles, for example.
[0066] As the metal particles, for example, metal single substance particles or alloy particles containing iron, cobalt, molybdenum, chromium or nickel can be cited. As alloy particles, iron-based alloy particles, cobalt-based alloy particles, molybdenum-based alloy particles, chromium-based alloy particles, and nickel-based alloy particles can be cited. Among them, cobalt-based alloy particles with excellent wear resistance are preferably used, and specifically, Co-28Mo-8Cr-2.5Si is preferably used.
[0067] Examples of the ceramic particles include tungsten carbide particles and aluminum oxide particles.
[0068] The average particle size (equivalent circle diameter) of the metal particles or ceramic particles is preferably 5 μm to 40 μm, more preferably 10 μm to 30 μm. If the average particle size of the metal particles or ceramic particles is less than 5 μm or exceeds 40 μm, it may not be possible to form a desired sliding film with good yield.
[0069] The average particle size (equivalent circle diameter: the diameter of a circle having the same area as the projected area of the particle image) of the metal particles or ceramic particles can be calculated by binarizing a scanning electron microscope image by image processing and analyzing the image.
[0070] (Method for manufacturing sliding member)
[0071] The sliding member can be produced, for example, by forming a sliding film on the substrate surface by cold spraying, in which raw material particles containing the titanium-containing copper-based alloy particles and the metal particles and ceramic particles added as needed are blown onto the substrate surface in a non-molten state.
[0072] In the titanium-containing copper-based alloy particles in the raw material particles, the oxygen content, including the titanium oxide layer on the particle surface, is preferably 0.1 mass % or more and 2.0 mass % or less, and more preferably 0.25 mass % or more and 0.8 mass % or less. In addition, when the oxygen content in the titanium-containing copper-based alloy particles in the raw material particles is less than 0.1 mass %, it is possible that the desired sliding film cannot be formed with a good yield. On the other hand, when the oxygen content in the titanium-containing copper-based alloy particles in the raw material particles exceeds 2.0 mass %, it is difficult to produce the titanium-containing copper-based alloy particles themselves.
[0073] The content of the metal particles or ceramic particles in the raw material particles is preferably 50% by mass or less. Within the above range, the content ratio of the titanium-containing copper-based alloy particles can be ensured, and the thermal conductivity of the sliding member can be ensured.
[0074] Cold spraying is a method in which raw material particles are collided with a substrate in a non-molten solid state together with an inert gas in a supersonic flow without melting or vaporizing the raw material particles, thereby forming a particle aggregate coating.
[0075] The raw material particles can be made by various methods. However, from the viewpoint of easily obtaining the raw material particles as solid solution particles, it is preferred to make the raw material particles by, for example, blowing water or gas onto the molten titanium-containing copper-based alloy to solidify the micronized droplets and form particles using a water atomization method or a gas atomization method. In order to obtain the desired oxygen content from the powder just after atomization, the water atomization method is preferred.
[0076] In cold spraying, when the titanium-containing copper-based alloy particles are solid solution particles, before the titanium-containing copper-based alloy particles in the solid phase collide with the substrate, the titanium-containing copper-based alloy particles have not yet precipitated and solidified, so the titanium-containing copper-based alloy particles undergo plastic deformation and absorb the stress of the collision, thereby preventing the titanium-containing copper-based alloy particles from breaking or rebounding.
[0077] In addition, within the copper-based alloy particles containing titanium, copper and titanium as solid solution components are reacted as Cu due to the energy of collision. 4 Compounds such as Ti precipitate to form crystallites having an average particle size of, for example, 5 to 50 nm, and the titanium-containing copper-based alloy particles become precipitation-solidified copper-based alloy particles, thereby improving wear resistance.
[0078] Then, through the collision of the raw material particles, part of the kinetic energy is converted into thermal energy, the surface of the raw material particles is locally melted and solidified, so that the raw material particles are combined with each other to form a particle aggregate containing titanium-copper-based alloy particles, and further to form a particle aggregate containing metal particles or ceramic particles added as needed in a dispersed state.
[0079] At this time, the surface of the raw material particles is partially melted, so diffusion occurs to generate precipitates such as intermetallic compounds. However, since the temperature of the substrate and the raw material particles is below the melting point of the raw material particles, the locally melted portion is quenched, so the crystal growth time of the precipitates is very short.
[0080] Therefore, nanocrystals or amorphous materials are formed near the interface where the substrate and the particles are bonded, or near the interface where the particles are bonded to each other.
[0081] The speed at which the raw material particles are blown is preferably 300 to 1200 m / s, more preferably 500 to 1200 m / s.
[0082] The pressure of the working gas for blowing the raw material particles is preferably 2 to 7 MPa, more preferably 3.5 to 7 MPa. When the pressure of the working gas is less than 2 MPa, the particle velocity may not be obtained, and the porosity may increase.
[0083] In addition, the temperature of the working gas also depends on the type and particle size of the raw material particles, but is preferably 400 to 1000°C, and more preferably 600 to 1000°C. When the temperature of the working gas is lower than 400°C, the raw material particles are difficult to plastically deform, the porosity increases, and the wear resistance may decrease. In addition, when the temperature of the working gas exceeds 1000°C, it is too close to the melting point of the raw material particles, and the throat of the injection nozzle is easily clogged.
[0084] Examples of the working gas include nitrogen gas and helium gas. These may be used alone or in combination.
[0085] The thickness of the sliding film is also dependent on the temperature of the part where the sliding part is used and the sliding environment, but is preferably, for example, 0.05 mm or more and 5.0 mm or less, and more preferably 0.1 mm or more and 0.5 mm or less. When the thickness of the sliding film is less than 0.05 mm, the strength of the sliding film itself is insufficient, and plastic deformation may occur when the strength of the substrate is low. In addition, when the thickness of the sliding film exceeds 5.0 mm, the sliding film may be easily peeled off from the substrate due to the relationship between the residual stress generated when the sliding film is formed and the interface adhesion.
[0086] Figure 3 The present invention is a partial cross-sectional view schematically showing a part of an embodiment of an internal combustion engine of the present invention. More specifically, the present invention is a partial cross-sectional view schematically showing a valve transmission mechanism including an engine valve. In the following embodiments, the same symbols are given to the same structural parts as those in the first embodiment or the second embodiment, and the detailed invention is omitted.
[0087] (internal combustion engine)
[0088] like Figure 3As shown, when the cam lobe 40 rotates, the valve lifter 41 is pressed down while compressing the valve spring 42, and the engine valve 43 is guided and pressed down by the valve guide 45 having the valve stem seal 44, so that the engine valve 43 leaves the seat 46A of the engine valve 43 on the cylinder head 46, and the exhaust port 47 is connected to the combustion chamber (open state of the engine valve). Then, when the cam lobe 40 rotates further, the engine valve 43 is pushed up together with the valve lifter 41, the retainer 48 and the cock 49 by the rebound force of the valve spring 42, and the engine valve 43 contacts the seat 46A, and the exhaust port 47 is disconnected from the combustion chamber (closed state of the engine valve). This opening and closing of the engine valve 43 is performed synchronously with the rotation of the cam lobe 40. Then, the valve stem 43A of the engine valve 43 is pressed into the valve guide 45 on the cylinder head 46 side and assembled while being lubricated with oil. In addition, the valve face 43B of the engine valve 43, which corresponds to the opening and closing valve portion of the combustion chamber (not shown), is in contact or non-contact state with the seat portion 46A of the engine valve 43 of the cylinder head 46 during operation. Figure 3 Although the exhaust port 47 side is shown in the figure, the sliding member of the present invention can also be applied to the intake port side which is not shown in the figure.
[0089] Moreover, a sliding component having the above-mentioned sliding film, such as the sliding component (1, 2) in the first or second embodiment, is applied to the sliding surface 46A of the seat portion 46A of the engine valve in the cylinder head, which is a sliding part of the cylinder head and the engine valve. As a result, the high-temperature wear resistance of the internal combustion engine can be improved. In addition, the internal combustion engine of the present invention can eliminate the press-fit type valve seat. As a result, the shape of the exhaust port and the intake port can be liberalized and the diameter of the engine valve can be enlarged, which can improve the fuel consumption, output power, torque, etc. of the engine.
[0090] Example
[0091] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0092] (Comparative Example 1)
[0093] As raw material particles, copper-based alloy particles containing nickel / silicon (composition: Cu-3Ni-0.7Si, particle size (D 50 ): 32.2μm), cold spraying was performed under the following conditions to form a sliding film on the surface of the aluminum alloy substrate to obtain the sliding part of this example. In addition, when forming a sliding film on the surface of the aluminum alloy substrate used for the valve seat single body knocking test, after forming a sliding film with a thickness of 0.4 to 0.5mm on the substrate, it was finished into the shape of the seat portion of the engine valve in the actual cylinder head by mechanical processing. In addition, the particle size (D50 The volume distribution was measured by a laser diffraction / scattering method using a particle size distribution measuring apparatus, Microtrac MT3000EXII, manufactured by Microtrac Bell Co., Ltd., and the median particle size was set to a particle size at which the cumulative frequency was 50%.
[0094] Cold spray equipment: PCS-1000 manufactured by Plasma Technology Co., Ltd.
[0095] Working gas: Nitrogen
[0096] Working gas temperature: 600℃
[0097] Working gas pressure: 4MPa
[0098] Spray distance: 20mm
[0099] Aluminum alloy substrate: Material type: A1050 specified by Japanese Industrial Standards, size: 100×100×5mm (for Vickers hardness test):
[0100] Material type: A5056 specified by Japanese Industrial Standards, size: In the state where the processing of the seating part of the engine valve of the cylinder head is completed, assuming that the target sliding film thickness is 0.2mm, pre-processing of the aluminum alloy substrate is performed, and the pre-processed aluminum substrate (for valve seat monomer knocking wear test) is prepared.
[0101] Substrate rotation speed: 300rpm
[0102] Gantt chart traverse speed: about 100mm / s
[0103] Raw material particle supply: about 7g / min
[0104] (Comparative Example 2)
[0105] As raw material particles, copper-based alloy particles containing nickel, cobalt, and silicon (composition: Cu-1.5Ni-1.5Co-0.7Si, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with particles having a particle size of 31.7 μm to obtain a sliding component of this example.
[0106] (Comparative Example 3)
[0107] As raw material particles, copper-based alloy particles containing nickel, cobalt, and silicon (composition: Cu-2.2Ni-0.8Co-0.7Si, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with particles of 0.3 μm and 0.5 μm, thereby obtaining a sliding component of this example.
[0108] (Comparative Example 4)
[0109] As raw material particles, the copper-based alloy particles containing iron and silicon (composition: Cu-3Fe-0.7Si, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1 to obtain the sliding component of this example.
[0110] (Example 1)
[0111] As raw material particles, titanium-containing copper-based alloy particles (composition: Cu-3.6Ti, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1 to obtain the sliding component of this example. Figure 4 This is a scanning electron microscope image of a cross section of the sliding film in this example.
[0112] (Example 2)
[0113] As raw material particles, the titanium-containing copper-based alloy particles (composition: Cu-5.3Ti, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1 to obtain the sliding component of this example.
[0114] (Example 3)
[0115] As raw material particles, titanium-containing copper-based alloy particles (composition: Cu-8.3Ti, particle size (D 50 The same operation as in Comparative Example 1 was repeated to obtain a sliding component of this example, except that the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1 were replaced with the nickel-silicon-containing copper-based alloy particles.
[0116] (Example 4)
[0117] As raw material particles, titanium-containing copper-based alloy particles (composition: Cu-10.4Ti, particle size (D 50 The same operation as in Comparative Example 1 was repeated except that the nickel-silicon-containing copper-based alloy particles were replaced with the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1 to obtain the sliding component of this example.
[0118] (Comparative Example 5)
[0119] As raw material particles, instead of the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1, nickel-silicon-containing copper-based alloy particles (composition: Cu-2.5Ni-0.7Si, particle size (D 50 ):33.1μm) and cobalt-based alloy particles (composition: Co-28Mo-8Cr-2.5Si, particle size (D 50 ):18.2 μm), and except that the mixing ratio (mass ratio) was 50:50, the same operation as in Comparative Example 1 was repeated to obtain the sliding component of this example.
[0120] (Comparative Example 6)
[0121] As raw material particles, instead of the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1, nickel-silicon-containing copper-based alloy particles (composition: Cu-3.5Ni-0.7Si, particle size (D 50 ):32.9μm) and cobalt-based alloy particles (composition: Co-28Mo-8Cr-2.5Si, particle size (D 50 ):18.2 μm), and except that the mixing ratio (mass ratio) was 50:50, the same operation as in Comparative Example 1 was repeated to obtain the sliding component of this example.
[0122] (Example 5)
[0123] As raw material particles, instead of the nickel-silicon-containing copper-based alloy particles used in Comparative Example 1, titanium-containing copper-based alloy particles (composition: Cu-3.6Ti, particle size (D 50 ):33.2μm) and cobalt-based alloy particles (composition: Co-28Mo-8Cr-2.5Si, particle size (D 50 ):18.2 μm), and except that the mixing ratio (mass ratio) was 50:50, the same operation as in Comparative Example 1 was repeated to obtain the sliding component of this example.
[0124] [Table 1]
[0125]
[0126] (Presence or absence of titanium oxide layer)
[0127] The presence or absence of a titanium oxide layer was confirmed by observing the cross section of the sliding film of each example using a scanning electron microscope and an energy dispersive X-ray analyzer. The obtained results are collectively shown in Table 1.
[0128] (Presence or absence of copper and titanium precipitates)
[0129] The presence or absence of copper and titanium precipitates (Cu4 The obtained results are also recorded in Table 1.
[0130] (Porosity and area ratio of metal particles / alloy particles / ceramic particles)
[0131] In each sliding film, the cross section was photographed in five fields of view within the image field of view of the scanning electron microscope mirror image, 350 μm horizontally and 263 μm vertically, and binarized using an image processing device to calculate the porosity. In addition, in the image, the area ratio of the metal single substance particles / alloy particles / ceramic particles was calculated, and the area ratio of the substrate particles was obtained as the remainder. The results are recorded in Table 1.
[0132] (Amorphous or nanocrystalline)
[0133] In the sliding film of each example, the diffraction pattern was projected onto the detector surface by electron beam backscatter diffraction of a scanning electron microscope, and the crystal orientation was analyzed based on the projected pattern to confirm whether there were amorphous or nanocrystals at the interface between the particles. In the sliding film of each example, the presence of amorphous or nanocrystals could be confirmed.
[0134] [Performance evaluation]
[0135] The performance of the sliding components of the above examples was evaluated under the following conditions. The obtained results are collectively recorded in Table 1.
[0136] (Vickers hardness test)
[0137] Test piece shape: 5×5×10mm
[0138] Measuring temperature: 20℃, 200℃, 300℃, 400℃
[0139] Measuring points: 5 points
[0140] Measuring load: 500gf
[0141] The average value of the Vickers hardness at the five points measured in the above-described manner was calculated.
[0142] (Valve seat monolithic knock wear test)
[0143] Equipment: Valve seat single body knocking wear test equipment (manufactured by Takachiho Seiki Co., Ltd.)
[0144] Test temperature: 300℃
[0145] Number of seats: 540,000 times (3000cpm×3hr)
[0146] Evaluation items: Valve seat wear (shape measurement)
[0147] As can be seen from Table 1, the sliding parts of Examples 1 to 5 belonging to the scope of the present invention have a Vickers hardness at high temperature (300°C, 400°C) harder than the sliding parts of Comparative Examples 1 to 6 outside the present invention. Therefore, as can be seen from Table 1, the sliding parts of Examples 1 to 4 belonging to the scope of the present invention, which do not contain any of metal single particles, alloy particles, and ceramic particles, have excellent high-temperature wear resistance compared to the sliding parts of Comparative Examples 1 to 4 outside the present invention, which do not contain any of metal single particles, alloy particles, and ceramic particles. Furthermore, as can be seen from Table 1, the sliding part of Example 5, which contains alloy particles and belongs to the scope of the present invention, has more excellent high-temperature wear resistance than the sliding parts of Comparative Examples 5 and 6 outside the present invention, which contain alloy particles.
[0148] The sliding member of the present invention has excellent high-temperature wear resistance, which is believed to be due to the following Figure 4 As shown, the sliding film contains copper-based alloy particles containing titanium, and has a linear titanium oxide layer at a part of the interface between the particles forming the sliding film.
[0149] It is also considered that the sliding member of the present invention has excellent high-temperature wear resistance because the titanium content in the copper-based alloy particles is 3.5 mass % or more and 11.0 mass % or less.
[0150] Furthermore, it is considered that the sliding member of the present invention has excellent high-temperature wear resistance because the copper-based alloy particles contain precipitates composed of copper and titanium.
[0151] Furthermore, the sliding member of the present invention has excellent high-temperature wear resistance, which is also considered to be because the sliding film contains the above-mentioned predetermined metal particles.
[0152] The present invention has been described above based on a plurality of embodiments, but the present invention is not limited thereto, and various modifications can be made within the scope of the gist of the present invention. For example, the above-mentioned constituent elements are not limited to the constituent elements shown in each embodiment, and the details of the specifications of the copper-based alloy particles, metal particles, ceramic particles, sliding films, etc. can also be changed, or the constituent elements of each embodiment can be applied to other embodiments.
[0153] For example, in the sliding component of the above embodiment, the case where the sliding film is formed on the surface of the base material is exemplified, but in the sliding component of the present invention, for example, the entire sliding component may be formed of the sliding film.
[0154] In addition, for example, in the internal combustion engine of the above-mentioned embodiment, an example is given of a case where a sliding component is provided on the seating portion (valve seat) of the engine valve, but in the internal combustion engine of the present invention, for example, a sliding component may be provided on at least one of the valve face of the engine valve, the valve stem, the valve guide, the valve lifter, the piston, the piston ring, the piston pin, the cylinder, the crankshaft, the camshaft, the connecting rod, etc.
[0155] Explanation of symbols
[0156] 1, 2: Sliding parts
[0157] 10: Base material
[0158] 20: Sliding film
[0159] 20a: Interface
[0160] 20b: Hole
[0161] 20c: Surface
[0162] 21: Copper-based alloy particles
[0163] 23: Titanium oxide layer
[0164] 25: Metal particles (ceramic particles)
Claims
1. A sliding component having a sliding film at least on its surface, characterized in that: The sliding film contains copper-based alloy particles containing titanium, and has a titanium oxide layer on a part of the interface between the particles forming the sliding film.
2. The sliding component according to claim 1, wherein: The titanium content in the copper-based alloy particles is 3.5 mass % or more and 11.0 mass % or less.
3. The sliding component according to claim 1, wherein: The titanium content in the copper-based alloy particles is 3.5 mass % or more and 9.0 mass % or less.
4. The sliding component according to claim 1, wherein: The copper-based alloy particles contain precipitates composed of copper and titanium.
5. The sliding component according to claim 2, characterized in that: The copper-based alloy particles contain precipitates composed of copper and titanium.
6. The sliding component according to claim 1, wherein: The sliding film includes metal particles and / or ceramic particles, and the metal particles contain at least one metal selected from the group consisting of iron, cobalt, molybdenum, chromium, and nickel.
7. The sliding component according to claim 1, wherein: The porosity of the cross section of the sliding film is 4 area % or less.
8. The sliding component according to claim 1, wherein: The sliding film has at least one of amorphous and nanocrystals at interfaces between particles forming the sliding film.
9. The sliding component according to claim 1, wherein: A substrate is provided, and the sliding film is formed on the substrate.
10. The sliding component according to claim 9, wherein: The sliding film is formed by blowing particles forming the sliding film onto the substrate and deforming the particles.
11. An internal combustion engine, characterized in that: A sliding member according to any one of claims 1 to 10 is provided.
